Capillary Water in Pericarp Enhances Hypoxic Condition during On-Tree Fruit Maturation That Induces Lignification and Triggers Translucent Flesh Disorder in Mangosteen (Garcinia mangostana L.) - Sompoch Noichinda; Kitti Bodhipadma; Siwaruth Kong-In (Journal of Food Quality)
Translucent flesh of mangosteen normally occurs during fruit ripening. Rainfall, after water stress, enhanced on-tree mature green fruit to develop translucent flesh disorder more frequently. Thus, this research pursued the effect of applied water on translucent flesh disorder development. The on-tree mature green stage fruits were selected and wrapped with 3 layers of fabric sheet. After that, water was continuously dropped (flow rate of 0.6 ml/min) on the wrapped sheet for 0, 1, and 2 days before picking. The results showed that duration time of water applying enhanced the increasing of water absorption significantly in peel. All of water-treated fruits ripened within 2-3 days after harvest and obviously had high lignin in secondary cell wall. It was hypothesized that lignification played an important role in hypoxia defense mechanism since the Na2CO3-SP fractionation extracted from alcohol insoluble residue (AIR) of translucent flesh aril was higher than those of normal aril. This Na2CO3-SP reinforced the strength of cell wall complexity as well as displaying the translucency character. Hence, we concluded that the capillary water (took place in intercellular air space of fruit pericarp) induced hypoxia tolerance mechanism that triggered translucent flesh disorder in mangosteen aril.